ANALYSIS OF FACTORS INFLUENCING CAREER INTEREST AS A PUBLIC ACCOUNTANT (Study on Accounting Graduates Who Have Worked) - Ni Made Ayu Wardani; Damayanti; Depita Anggraini (RADJA PUBLIKA, 2025)
This research aims to analyze the influence of Financial Rewards, Professional Training, Self-Motivation, and Gender on the career interest in becoming Public Accountants among Accounting Graduates who are already employed. The study utilized a random sampling method, involving 211 employed Accounting Graduates who responded to the research questionnaire. Data analysis was carried out using SPSS version 26 and employed multiple linear regression. Hypothesis testing was conducted using the T-test, F-test, and R-squared test. The findings indicate that Financial Rewards (X1), Professional Training (X2), Self-Motivation (X3), and Gender (X4) significantly affect the career interest in becoming Public Accountants among the participants. The results further reveal that these independent variables collectively explain 64.11% of the variance in career interest, while the remaining percentage is attributed to other factors not included in this study.